Suitability of various heat transfer fluids for high temperature solar thermal systems. (August 2019) - Vutukuru, Ravindra; Pegallapati, A. Saikiran; Maddali, Ramgopal
Highlights: Hitec XL and helium perform best in terms of required length and heat transfer area. At high temperatures, pumping power required for gases is higher than liquid fluids. s-CO2 performs best in terms of fluid inventory cost, essential for setting field. For gaseous fluids, the effect of operating pressure on Figure of merit is marginal. Abstract: In recent years there is a huge interest in developing high temperature, solar thermal systems for power generation. Selection of suitable heat transfer fluid is an important requirement for these applications. This paper presents a comparative study between various heat transfer fluids suitable for high temperature solar thermal systems. The comparison is made on the basis of equal heat transfer rate, temperature rise of the heat transfer fluid and pressure drop per unit length in a typical solar absorber tube. Using simple friction factor and heat transfer correlations, equations for diameter ratio, heat transfer coefficient ratio, area ratio, length ratio, fluid pumping power ratio and fluid inventory cost ratio are obtained for various fluids, taking supercritical CO2 as the reference fluid. Figure of merit (FOM) ratio is also calculated using available equations. It is observed that liquid heat transfer fluids and molten salts offer better performance in the intermediate temperature range of around 150–550 °C. However, currently gaseous fluids (e.g. CO2 or He) are the only alternatives for temperatures beyond 550 °C. Supercritical CO2 offers the best performance in terms of cost of fluid inventory, which can be a major consideration in large output solar fields.